ENGAGEMENT BETWEEN TRADITION AND MODERNITY - Teaca, Mihaela Ioana (International Journal of Legal and Social Order, 2025)
For the life of a couple, engagement represents a stage preceding marriage, being the solemn promise to found a family. For the life of a couple, engagement represents a stage preceding marriage, being the solemn promise to found a family. In the traditional collective mentality, its value is supported by the social function, being in fact an understanding between families, as basic elements of the local community. In modern society, the social character of engagement has faded greatly, its role being mainly to externalize the marriage commitment, to express the feelings of the future spouses. The institution of engagement is regulated normatively, after years of lack of interest on the part of the legislator, but it has proven lenient with the sanctions applied, so that engagement is an institution known and loved by all, but too little protected, so that it does not have a more symbolic character.